Potentiometric Polymeric Film Sensors Based on 5,10,15-tris(4-aminophenyl) Porphyrinates of Co(II) and Cu(II) for Analysis of Biological Liquids - Larisa Lvova; Roberto Paolesse; Corrado Di Natale; Arnaldo D'Amico; Alberto Bergamini (International Journal of Electrochemistry)
Novel carbonate-selective potentiometric sensors based on 5,10,15-tris(4-aminophenyl)-20-phenyl porphyrinates of Cu(II) and Co(II) have been developed. Ionophore functioning mechanism and possible source of carbonate sensitivity have been evolved. Potentiometric properties of Co(II)- and Cu(II)TATPP-based sensors were compared with common carbonate-ISEs containing trifluoroacetophenone derivatives. The analytical utility of newly developed sensors has been demonstrated by measuring the bicarbonate content in human blood plasma.